Atrial fibrillation burden, episode duration and frequency in relation to quality of life in patients with implantable cardiac monitor. (June 2021) - Jansson, Victoria; Bergfeldt, Lennart; Schwieler, Jonas; Kennebäck, Göran; Rubulis, Aigars; Jensen, Steen M.; Raatikainen, Pekka; Sciaraffia, Elena; Blomström-Lundqvist, Carina
Highlights: Assessing the relationship between atrial fibrillation and quality of life. Implantable loop recorders assessed rhythm continuously in symptomatic patients. Atrial fibrillation burden, episode duration and frequency were included. Higher atrial fibrillation burden was associated with impaired quality of life. Abstract: Aims: To assess the relation between atrial fibrillation (AF) characteristics and health-related quality of life (QoL), and which AF characteristic had the greatest impact. Method: The AF characteristics burden (percentage of time in AF), duration and number of AF episodes/month were obtained from implantable cardiac monitors during the 2-month run-in period in 150 patients included in the randomized CAPTAF trial comparing early ablation and antiarrhythmic drug therapy. The QoL was measured by the General Health and Vitality dimensions of the 36-Item Short-Form Health Survey. AF characteristics were analysed continuously and in quartiles (Q1-Q4). Results: Greater AF burden (p = 0.003) and longer AF episodes (p = 0.013) were associated with impaired QoL (Vitality score only) in simple linear regression analyses. Greater AF burden was, however, the only AF characteristic associated with lower QoL, when adjusted for sex, type of AF, hypertension, heart rate above 110 beats per minute during AF, and beta-blocker use in multiple linear regression analyses. For every 10% increase in AF burden there was a 1.34-point decrease of Vitality score (95% confidence interval (CI) −2.67 to −0.02, p = 0.047). The Vitality score was 12 points lower (95% CI −22.73 to −1.27, p = 0.03) in patients with an AF burden > 33% (Q4) versus those with < 0.45% (Q1), but only in unadjusted analysis. Conclusion: AF burden had a greater impact on QoL (Vitality), than the duration and number of AF episodes, corroborating that AF burden may be the preferred outcome measure of rhythm control in trials including relatively healthy AF populations.